Staffing models in the cardiac intensive care unit. Issue 4 (27th August 2022) - Quien, Mary; Thomas, Alexander; Ludmir, Jonathan; Miller, P. Elliott
Abstract : Purpose of review: The modern cardiac intensive care unit (CICU) has evolved into a high-intensity unit that cares for critically ill patients. Despite this transformation, changes to the staffing model and organizational structure in these specialized units have only recently begun to meet these challenges. We describe the most recent evidence which will inform future CICU staffing models. Recent findings: In the United States, the majority of CICUs are open as opposed to closed units, yet recent data suggests that transition to a closed staffing model is associated with a decrease in mortality. These reductions in mortality in closed CICUs are most pronounced in the most critically ill populations, such as patients with mechanical circulatory support, cardiac arrest, and respiratory failure. In addition, one study has shown that transition to a cardiac intensivist staffed CICU was associated with a reduction in mortality. Finally, multidisciplinary and protocolized teams imbedded within the CICU, specifically 'shock teams, ' have recently been developed and may reduce mortality in this particularly sick patient population. Summary: Although the preponderance of data suggests improved outcomes with a closed, intensivist staffed CICU model, future multicenter studies are needed to better define the ideal staffing models for the contemporary CICU.